Analisis Strength, Weakness, Opportunity, and Threats Pembinaan Prestasi Training Center Kabupaten Ponorogo - Hermin Adi Bakhrudin; Made Pramono (Pusat Riset dan Inovasi Nasional, 2023)
Efforts to achieve and maintain an achievement are closely related to the quality of sports coaching provided, one of which is through a training center. The Ponorogo Regency athletics training center is still relatively new, for this reason this study aims to determine (SWOT) the strengths, weaknesses, opportunities, and threats of the Ponorogo Regency athletics training center. The method used is descriptive qualitative with data collection techniques in the form of interviews with the chairman of the board, two trainers, and six athletes from the Ponorogo District athletics training center. The results showed that strength is obtained from training program factors that have been arranged according to the needs of athletes because of the selection of competent trainers and the recruitment of athletes who are carried out thoroughly so that it has the potential to become an opportunity for increased achievement in subsequent activities. Weaknesses are dominated by the lack of adequate facilities and infrastructure. This is in line with the threat that government support for facilities and infrastructure is still lacking, which has the potential to reduce athletes' interest in participating in training.